Qualitative study of prosthetic suspension systems on individuals with transtibial amputations aatisfaction and perceived problems with their prosthetic devices - Ali, S.; Abu Osman, Noor Azuan; Naqshbandi, M.M.; Eshraghi, A.; Kamyab, M.; Gholizadeh, H. (2012)
Abstract Ali S, Abu Osman NA, Naqshbandi MM, Eshraghi A, Kamyab M, Gholizadeh H. Qualitative study of prosthetic suspension systems on transtibial amputees' satisfaction and perceived problems with their prosthetic devices. Objective To investigate the effects of 3 dissimilar suspension systems on participants' satisfaction and perceived problems with their prostheses. Design Questionnaire survey. Setting A medical and engineering research center and a university biomedical engineering department. Participants Persons with unilateral transtibial amputation (N=243), using prostheses with polyethylene foam liner, silicone liner with shuttle lock, and seal-in liner. Interventions Not applicable. Main Outcome Measures Descriptive analyses were performed on the demographic information, satisfaction, and prosthesis-related problems of the study participants. Results The results showed significant differences between the 3 groups regarding the degree of satisfaction and perceived problems with the prosthetic device. Analyses of the individual items revealed that the study participants were more satisfied with the seal-in liner and experienced fewer problems with this liner. The silicone liner with shuttle lock and seal-in liner users reported significant differences in maintenance time compared with the polyethylene foam liner. Users of the silicone liner with shuttle lock experienced more sweating, while those who used the seal-in liner had greater problems with donning and doffing the device. Conclusions The results of the survey provide a good indication that prosthetic suspension is improved with the seal-in liner as compared with the polyethylene foam liner and silicone liner with shuttle lock. However, further prospective studies are needed to investigate which system provides the most comfort and the least problems for participants.